FLOW IN A CATHETERIZED EXPONENTIALLY DIVERGING TUBE WITH A PERIPHERAL LAYER OF DIFFERENT VISCOSITY BY MEANS OF PERISTALTIC WAVES OF DILATING AMPLITUDE - Pandey S.K.; Pandey A.K. (My University, 2025)
In this paper, we investigate the impact of catheterization on swallowing if esophagus suffers from a hiatus hernia. It is modeled as a partially diverging tube having a peripheral layer of different viscosity besides the core layer. The model duly considers mass conservation in the two layers separately. It is inferred that even in the presence of a catheter inside esophagus, any sliding herniation requires less pressure for flow, i.e., swallowing will be easier if the esophagus diverges more near the cardiac sphincter. However, the presence of a catheter requires esophagus to work more in order to swallow the same quantity. Pressure enhances by many folds, but its distribution remains similar. The time-averaged flow rate and the maximum pressure, restraining fluid from swallowing, give some clues about a catheterized herniated esophagus. The flow enhances for a thinner peripheral layer. A more viscous peripheral layer as well favors flow. However, the thickness of the catheter hinders swallowing. This is to be taken care of while a patient undergoes any catheterized treatment. Increasing wave amplitude and dilating parameters can enhance flow in the presence of a catheter. It is also concluded that the frictional forces exerted by the tube wall on the peripheral layer increase in the catheter's presence. © 2024 World Scientific Publishing Company.